Shift Knowledge in Energy Transition Era - Indradewa, Rhian (SAFE-Network, 2022)
This study proposes a strategy for managing knowledge shifting processes when a company's vision and mission evolve in tandem with the expansion of its strategy, business processes, and organizational architecture in response to environmental challenges and legislation. This paper is based on a case study of Pertamina, an Indonesia energy company. This paper used survey-based quantitative research. The findings revealed that companies must transfer their knowledge in order to successfully expand their business reach. The process of knowledge transfer will contribute to the success of the new business. Information shifting procedures can be accomplished by developing new knowledge that differs from existing business knowledge. Managing existing employees with new knowledge and managing new employees with new information are the two components of the knowledge transfer process. The elements of shift mentality, willingness to learn, teamwork, and age have a role in guiding existing employees to acquire new skills. In managing the new employee, the organization is able to hire new employees with new knowledge and select new employees with diverse educational backgrounds and experiences that match the expanded business scope. This research examined the process of knowledge transfer via the lens of Knowledge-Based View (KBV) theory.